Quercetin-Glycolic Acid Cocrystalization Using Solvent Evaporation and Slurry Methods - Barikah, Kuni Zu'aimah; Wicaksono, Yudi; Wisudyaningsih, Budipratiwi (Indonesian Journal of Pharmaceutical Science and Technology, 2024)
Quercetin is a flavonoid compound with the highest antioxidant activity and has the potential to treat various diseases. However, quercetin has poor solubility in water which causes low bioavailability of the drug in the body. One of the modifications that can be made to improve the solubility of a drug is solid modification, for example cocrystals. Cocrystal is a crystalline system between drug and coformer which interacts through hydrogen bonding. Glycolic acid is a compound that can function as a coformer because it has functional groups that have the potential to interact through hydrogen bonds with quercetin molecules. Quercetin-glycolic acid cocrystals were prepared in two molar ratios, namely 1:1 and 1:2, and through two methods of preparation, namely solvent evaporation and slurry. The results of the crystallinity analysis and thermal analysis of the sample indicated that a new solid phase was formed in the sample that was specific and different from the two constituent components. Samples with a molar ratio of 1:2 and the slurry preparation method are known to be samples with the most optimal new crystalline phase formation.